Self-Assessment of Listening Competence on the Basis of Analysis of its Effective Composition at the Master’s Stage of Professional Training (Journal of Educational Sciences, 2020)
The standard for postgraduate education “Master” makes high demands on the communicativecompetencies of future specialists, which requires attention to the development of listening skills forundergraduates. Meanwhile, teachers and undergraduates are not adequately provided with methods formonitoring the quality of listening.Aim: to develop a questionnaire for self-assessment of the competence of the listening, reflectingthe effective composition of the listening. The main idea is to develop a diagnostic tool based on thestudy of the system of options for listening activities described by experts and analysis of the effectivecomposition of the diagnosed competency.The scientific significance of the work lies in the systematization and author’s classification of theoptions for listening. Practical significance is in creating a new quality self-assessment tool of one of thebasic competencies.The study used methods of theoretical analysis and synthesis, empirical methods of observation,conversation, and survey.The study allowed to systematize and classify models of listening activity; showed that the quality ofself-esteem can be improved by using questionnaires that reflect the effective composition of listeningoptions; allowed to determine the effectiveness of the developed methodology.The study is a contribution to the development of didactics of postgraduate education and has prospectsfor further development.Key words: self-assessment of the competence of a listening in a magistracy.